2018
DOI: 10.1177/1352458518786650
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mindfulness-based stress reduction for people with multiple sclerosis at 8 weeks and 12 months: A randomized clinical trial

Abstract: Emotional well-being improved with both MBSR and education. Spontaneous improvement cannot be ruled out as an explanation for findings and additional studies that evaluate the impact of mindfulness training to improve emotional health are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 38 publications
(68 reference statements)
1
58
0
Order By: Relevance
“…Twelve RCTs were identified as eligible for inclusion in the systematic review. [21][22][23][24][25][26][27][28][29][30][31][32] However, only eight studies reported endpoint data that could be included in the meta-analysis. 21-24 28-30 32 (figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twelve RCTs were identified as eligible for inclusion in the systematic review. [21][22][23][24][25][26][27][28][29][30][31][32] However, only eight studies reported endpoint data that could be included in the meta-analysis. 21-24 28-30 32 (figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies took place in Iran, 23 25-27 29 three in the UK, 22 28 31 two in Italy, 24 32 one each in Switzerland 30 and the USA. 21 Six studies reported assessing a MBI against usual care, 22 23 28-31 in three this was not specified, [22][23][24] while three used an active comparator (psychoeducation control). 21 24 32 Six studies were powered.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations